Edible oils adulteration analysis by fiber optic multimode displacement sensor - Haroon, Hazura; Nordin, Siti Noraminah; Anbalagan, Thanigai; Othman, Maisara (National Institute of Optoelectronics, 2022)
A fiber optic sensor has been developed to detect the adulteration in edible oil, particularly coconut oil. In this paper, the sensing mechanism uses MMF-MMF based on displacement sensors by employing the lateral offset method. The distance offset set were 4.42 μm, 7.49 μm, and 7.83 μm. The refractive index for pure coconut oil, paraffin oil, and palm oil are found to be 1.4481, 1.4585, and 1.4634 respectively. The sensitivity of each sensor was determined by referring to the highest offset distance of each fiber. Upon completion, the highest sensitivity was observed for 7.83 µm lateral offset distance which is 0.406 dBm/mol for palm oil detection and 0.437 dBm/mol for paraffin oil detection. The experimental results proved that the larger the offset distance, the higher the sensitivity of the fiber sensor.